Oddziaływania psychoedukacyjne a wiedza o sobie dorosłych osób ze spektrum autyzmu = A psycho-educational interventions and selfknowledge of people on the autism spectrum - Kanar. Mirosława (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the study was to determine the relevance of psychoeducational interventions to the self-knowledge of adults on the autism spectrum. This study assumes that the interpretative paradigm is crucial in order to seek answers to the researcher?s research questions. Autistic individuals tend to have difficulties in the communication sphere as well as in the social sphere. Therefore, an individual approach to each participant proved to be particularly important. The analysis and interpretation of the empirical material involved a phenomenographic perspective.
Keywords: oddziaływanie psychoedukacyjne; terapia; wiedza o sobie; spektrum zaburzeń autystycznych; autyzm; psycho-educational interventions; therapy; self-knowledge; autism; autism spectrum disorder